PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS IV SD NEGERI 241 PALEMBANG - Rihayah Rihayah (Universitas Negeri Medan, 2021)
Abstract: Application Of Cooperative Learning Model Type Of DiscoveryLearning In Increasing Science Learning Outcomes In Class IV Students SDNegeri 241 Palembang. The purpose of this action research is to determine theincrease in student learning outcomes after the implementation of the DiscoveryLearning Type Cooperative Learning Model. This study uses two rounds of actionresearch (classroom action research). Each round consists of four stages, namely:design, activities and observations, reflection, and revision. The location of thisclassroom action research was carried out at SD Negeri 241 Palembang, SouthSumatra province. This research was conducted from February to April 2019 forthe 2018/2019 academic year. The subjects of this study were students of classIV.A SD Negeri 241 Palembang, totaling 30 students. The main topic ofdiscussion was about the material